On the acoustical relevance of supraglottal flow structures to low-frequency voice production - Zhang, Zhaoyan (Acoustical Society of America, 2010)
The supraglottal flow exhibits many complex phenomena such as recirculation, jet instabilities, jet attachment to one vocal fold wall, jet flapping, and transition to turbulence. The acoustical relevance of these flow structures to low-frequency voice production was evaluated by disturbing the supraglottal flow field using a cylinder and observing the consequence on the resulting sound pressure field. Despite a significantly altered supraglottal flow field due to the presence of the cylinder, only small changes in sound pressure amplitude and spectral shape were observed. The implications of the results on our understanding of phonation physics and modeling of phonation are discussed.